Pemberian Makanan Tambahan (PMT) Berbasis Kearifan Lokal Sebagai Upaya Pencegahan dan Penanganan Stunting Pada Balita di Desa Parang Baddo Kecamatan Polongbangkeng Utara Kabupaten Takalar Provinsi Sulawesi Selatan - Pratama, Adi Putra; Harma, Asmarani; Latief, Mutmainnah (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Stunting is a condition where a toddler has less length or height compared to children his age. Stunted toddlers are a chronic nutritional problem caused by many factors, such as socio-economic conditions, maternal nutrition during pregnancy, pain in babies, and lack of nutritional intake in babies. The formula given to children who experience malnutrition according to the standards set by the World Health Organization (WHO) is made from oil, sugar, milk, water and flour. Apart from that, PMT can be made yourself with a composition that contains energy intake, protein and is made from ingredients that are easily obtained by the public at an affordable cost. These ingredients can be replaced with local food ingredients which are rich in vitamins and protein. The results of Monitoring the Nutritional Status (PSG) of Toddlers in 2017 by the Ministry of Health showed that 17.8% of toddlers experienced nutritional problems, including 3.8% cases of malnutrition and 14% malnutrition (Ministry of Health of the Republic of Indonesia, 2018). Meanwhile, based on the 2018 Riskesdas, cases of malnutrition reached 3.9% and cases of malnutrition reached 13.88% (Ministry of Health of the Republic of Indonesia, 2018). The prevalence of stunting in South Sulawesi Province in 2022 will be at 27.2 percent. Jeneponto Regency is the area with the highest stunting prevalence in South Sulawesi in 2022, reaching 39.8 percent, an increase of 1.9 percentage points from the stunting prevalence in 2021. Tana Toraja Regency is in second place with the largest stunting prevalence at 35.4 percent. Pangkajene and Islands Regency was 34.2 percent. Takalar Regency is still listed as an area with a high stunting prevalence rate, but recently it has decreased significantly. Based on data from the Indonesian Nutrition Status Study (SSGI) in 2022, the prevalence of stunting in Takalar Regency is at 31.1 percent. This figure has decreased significantly compared to 2021 of 34.7 percent.